2021
DOI: 10.21776/ub.jiae.009.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Household Poverty Status in Kediri City

Abstract: Analyses of the causes and the characteristics of poverty at micro levels provide more efficient strategies for the attainment of main Sustainable Development Goals. This study aimed to analyze the extent to which the characteristics of individuals, households, and communities influence the probability of household poverty status. The 2019 Social Welfare Integrated Data and Village Potential Data of Kediri City were analyzed using an ordered logit regression model and then interpreted based on marginal effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…This relationship is statistically significant at the 1% level. These findings are consistent with our hypothesis as well as previous research of Dwi Yennie et al [45] and Balogun et al [46]. This is because maize is a subsistence crop that provides both food and income to households, making it an essential part of their livelihood strategies.…”
Section: Results and Discussion On Factors Influencing Smallholders F...supporting
confidence: 94%
“…This relationship is statistically significant at the 1% level. These findings are consistent with our hypothesis as well as previous research of Dwi Yennie et al [45] and Balogun et al [46]. This is because maize is a subsistence crop that provides both food and income to households, making it an essential part of their livelihood strategies.…”
Section: Results and Discussion On Factors Influencing Smallholders F...supporting
confidence: 94%
“…The result reveals that women are more likely to fall into poverty when there are more economically inactive people in their families, which puts a strain on consumption resources. This result is consistent with the empirical findings of Dwi et al (2021), Chaudhry et al (2019), Jayamohan and Kitesa (2014), Mohammed (2017) and Teka et al (2019).…”
Section: Resultssupporting
confidence: 92%
“…Age has a positive and significant effect and is directly related to women's poverty at a 1% probability level, suggesting that younger women in this study (18-30 years old) are more likely to be poor because they have fewer assets. This result is in line with the empirical findings of Dwi et al (2021) and Elias et al (2018) while conflicting with Sugiharti and Primanthi's (2017) finding who reported the negative coefficient for the cause-effect relationship between age and poverty. The number of dependents living with women has a direct and significant effect on women's poverty at a less than 1% probability level.…”
Section: Determinants Of Women's Povertysupporting
confidence: 85%
“…It was revealed there are many factors that can affect a person's working status and household poverty. Some of these factors include the availability of job opportunities in a given area, an individual's level of education and job skills, and the individual's personal circumstances (such as caring for children or other family members) (Khusaini, Prasetyia & Rozanti, 2021). In addition, larger societal factors, such as the overall state of the economy and government policies on issues such as minimum wage, can also play a role in working status and household poverty.…”
Section: Resultsmentioning
confidence: 99%